Epoxidation of (+/-)-7,8-dihydroxy-7,8-dihydrobenzo[a]pyrene during (bi)sulfite autoxidation: activation of a procarcinogen by a cocarcinogen. - Reed, G A (1986)
The (bi)sulfite ion undergoes extensive autoxidation in neutral aqueous media with the formation of sulfur trioxide radical anion that is detected by ESR. The radical anion subsequently reacts with molecular oxygen to form a peroxyl radical. We find that when (+/-)-trans-7,8-dihydroxy-7,8-dihydrobenzo[a]pyrene (BP-7,8-diol) is included in this autoxidation system, BP-7,8-diol is converted to diolepoxides, ultimate carcinogenic derivatives of benzo[a]pyrene. This epoxidation occurs with a stereoselectivity consistent with either a peroxyl radical or a peracid as the epoxidizing agent. The epoxidation is dependent on the concentration of both (bi)sulfite and oxygen. In the presence of 10 microM butylated hydroxyanisole, which abolishes (bi)sulfite autoxidation, no (bi)sulfite-dependent epoxidation occurs. These results are discussed in regard to the mechanism of (bi)sulfite autoxidation, and in relationship to the cocarcinogenicity of sulfur dioxide [anhydrous (bi)sulfite] for benzo[a]pyrene-induced pulmonary neoplasia.